Landslide Hazard Assessment and Zoning Using LIM Model by GIS in Givi Chay Watershed, Ardebil - Aghil Madadi; Behnam Noee; Abazar Esmali (نشریه جغرافیا و برنامه‌ریزی, 2013)
Identifying of impact factors in occurrence landslides of and hazard zoning is basic instrument for controlling this Phenomenon. Aim of this research is the assessment of the effective factors in landside occurrence and mapping it by using landside index model (LIM). For above pepouse", 11 important factors in mapping of landslide were evaluated and recognized by field working. Then landslide hazard zoning was performed by landside index model on the basis of 11 factors weight. After calculating of these factors (altitude classes, slope gradient, slope orientation, network dantsity, distance from river, distance from road, lithology, distanse from fault, vegetation cover, land use, annul rainfall and soil hydraulic group), final map was commutated from algebraic overlaying of 11-layers and there by final weight map was obtained. Study and analysis of 11-raster map, and important factors in Givi Chay watershed landslides using LIM Method showed that area with annual 375-405 mm precipitation had more influence in landslide occurrence. Also altitude classes between 1512-1927m area with low vegetation, area with high permeable soils and slopes with east and northeast orientation higher influence in occurrence.